The human auditory system: fundamental organization and clinical disorders - Aminoff, Michael J.; Boller, François; Swaab, Dick Frans (Handbook of clinical neurology, 2015)
The Human Auditory System: Fundamental Organization and Clinical Disorders provides a comprehensive and focused reference on the neuroscience of hearing and the associated neurological diagnosis and treatment of auditory disorders. This reference looks at this dynamic area of basic research, a multidisciplinary endeavor with contributions from neuroscience, clinical neurology, cognitive neuroscience, cognitive science communications disorders, and psychology, and its dramatic clinical application. -- Provided by publisher
Includes index. - Online resource; title from title description page (ScienceDirect, viewed March 10, 2015)
Keywords: Electronic books